Solution of a Class of Fourth Order Singular Singularly Perturbed Boundary Value Problems by Haar Wavelets Method and Quintic B-Spline Method (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, Haar wavelet method is described for solving a class of fourth order singular singularly perturbed boundary value problems. Its efficiency is tested by solving two examples for which the exact solution is known. Numerical comparisons have been carried out to demonstrate the efficiency and the performance of the proposed method.
Keywords: Boundary value problem; Haar wavelet; Quartic B-spline; Collocation point; Grid point